A serendipitous journey to a promoter variant: The c.‐106C>A variant and its role in late‐onset ornithine transcarbamylase deficiency. Issue 4 (12th April 2022) - Hertzog, Ashley; Selvanathan, Arthavan; Halligan, Rebecca; Fazio, Timothy; de Jong, Gerard; Bratkovic, Drago; Bhattacharya, Kaustuv; Tolun, Adviye Ayper; Bennetts, Bruce; Fisk, Katrina
Abstract: Ornithine transcarbamylase deficiency (OTCD) is an X‐linked urea cycle disorder characterised by reduced or absent OTC enzyme activity, resulting in the accumulation of neurotoxic ammonia. Approximately 80%–90% of the causative variants are identified by Sanger sequencing or multiplex ligation‐dependent probe amplification (MLPA) of the OTC gene. A 23‐year‐old male with biochemical evidence of OTCD was referred for molecular analysis. Initial Sanger sequencing yielded no pathogenic variants. MLPA testing raised suspicion of a mosaic deletion of exon 1; however, high‐resolution microarray did not identify a copy number variant on the X chromosome. Sequencing over the suspected breakpoint detected a hemizygous likely pathogenic promoter variant, c.‐106C > A, which was located within the MLPA probe binding site. Subsequently, historical patients referred to our centre, without a molecular aetiology for their OTCD, were re‐sequenced with these primers and this variant was also identified in two additional unrelated males. All three patients described in this case series have the late‐onset disease. Two presented at 5 years of age with vomiting, whilst the other was managed from birth based on a family history of late‐onset OTCD. One patient required liver transplantation due to recurrent decompensations; the other two are managed with a protein‐restricted diet. All three patients have not sustained any significant neurological insults and are functioning well as adults. These cases support screening of the promoter region within the OTC gene, particularly if a molecular basis has not been elucidated by MLPA or sequencing of the coding regions.